A hybrid immersed‐boundary/body‐fitted‐grid method and its application to simulating heart valve flows. (11th August 2022) - Wang, Jingyang; Zhou, Chunhua; Ai, Junqiang
Abstract: In this article, a hybrid immersed‐boundary (IB)/body‐fitted‐grid (BFG) method is presented for simulating flows with immersed moving boundaries. In this method, the stationary solid boundaries are treated by the BFG method while the moving boundaries are treated by an immersed boundary method named the local domain‐free discretization method. The hybrid IB/BFG method has both the advantage of an IB method in handling the moving boundaries and that of a BFG method in handling the stationary boundaries and the boundary layers over them. The present method is beneficial to heart valve flows where the leaflets are implanted in a blood vessel. For the simulation of pulsatile heart valve flows, a technique of driving force is proposed to maintain the conservation of the mass flux and improve the convergence of the pseudo‐time iteration in dual‐time‐stepping. The wall‐modeled large eddy simulation is employed for simulating turbulence. Numerical experiment is first performed for the pulsatile flow through a curved, pipe bend. To demonstrate the ability of the proposed method to simulate flows with complex, immersed boundaries, pulsatile physiological flows through a bileaflet mechanical heart valve mounted in a model straight aorta are calculated. The predicted results show good agreements with the published experimental data and numerical results. Abstract : Stationary boundaries are treated by the body‐fitted‐grid method while moving boundaries are treated by an immersed‐boundary method named the local domain‐free discretization method. To simulate pulsatile flows, a driving force is added into the momentum equations to maintain the instantaneous propagation of mass flux and improve the convergence of pseudo‐time iteration in dual‐time‐stepping. Physiological flows through a mechanical, bileaflet heart valve are calculated on a coarse grid and the results are comparable with the referenced experimental and numerical results.